Analisis Gaya Bahasa dan Sudut Pandang dalam Cerpen “Sepotong Senja Untuk Pacarku” dalam Sastra Siber pada Website www.medium.com - Senny Saikha Maharani (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study is motivated by the development of literature that has shifted to the digital realm, including the short story "Sepotong Senja Untuk Pacarku" by Seno Gumira Ajidarma which was republished on the website www.medium.com. The purpose of this study is to analyze the language style and point of view in the short story. This short story has a distinctive storytelling style, with the use of figurative language and poetic diction as the main attraction. The method used is qualitative descriptive with a stylistic approach and literature study techniques. The results of the analysis show that the dominant language styles in this short story include metaphor, personification, hyperbole, simile, litotes, euphemism, and epistolary. These language styles strengthen emotional expression and deepen the meaning of the story. In addition, the first person singular point of view creates a personal and intimate effect, so that the reader feels directly involved in the narrative of the character "I". This short story also shows the power of imaginative visualization in the context of cyber literature which allows the reading experience to be more interactive and reflective. This study concludes that SSUP's short story successfully utilizes the power of style and point of view to convey messages of love, longing, and existence deeply in a distinctive digital format.